Penyuluhan Pentingnya Manajemen Beban Tas Yang Ergonomis Bagi Pertumbuhan Dan Kesehatan Siswa Sekolah di SMAN 72 Jakarta Utara - Hendy Tannady (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The odd semester of the academic year 2022 is an important moment for education in Indonesia. After almost three years, students and teachers carried out online learning and teaching processes, finally in the odd semester of academic year 2022, schools especially in province of DKI Jakarta will implement onsite teaching and learning processes. Students will wake up early, prepare and bring their books and bags to their school. One thing that is identical with education in Indonesia is the large number of textbooks that students will carry in their bags, even though the load from the bag will have a long-term negative effect on bone growth and have an bad impact on student’s body posture. This is a point of concern for parents and teachers at SMAN 72 North Jakarta, at the invitation of the school, the author then provided a workshop about the importance of using ergonomic bags for students in order to maintain students' physical and psychological health. The result of this community service activity is a measurement of the satisfaction of the participants, 97.44% of 156 participants were very satisfied and assessed that the workshop gave them benefits in providing new knowledge about ergonomic bags.